Approaches of General and Specialist Dentists to Deep Caries Management: A Cross-Sectional Study from Turkey - Delikan, Ebru; Ertürk-Avunduk, Ayşe Tuğba; Aksu, Seçkin (UI Scholars Hub, 2021)
Objective: To determine the differences in treatment strategies and material preferences for deep dentine carious lesions (DDCLs) management among general and specialist dentists. Methods: Dentists working in universities, oral and dental health centers, or private practice were administered a 14-item web-based questionnaire regarding demographic and occupational characteristics, approaches to DDLCs, pulp capping methods, and preferences for restorative materials. The data were examined using descriptive statistical analysis and Pearson’s chi-square tests. Results: The study enrolled 298 general and 265 specialist dentists among whom 67.1% were female and 73.3% were aged 25 to 35 years. Total excavation and permanent restoration of DDCLs were the commonly preferred treatments (67.0%), although the pediatric dentists tended toward selective caries removal in these lesions. Mineral trioxide aggregate was used more regularly by the pediatric dentists and endodontists. The pediatric dentists exhibited statistically significantly lower preference for canal treatment than general dentists and endodontists as treatment option for mature teeth with DDCLs (p<0.05). Conclusion: Conservative treatment approaches and material preferences of specialists and general dentists in DDCLs are generally different. The age of dentists, the time since their graduation, place of work and the number of patients they have seen daily may affect the approaches and preferences.